A Candidate Prognostic Biomarker Complement Factor I Promotes Malignant Progression in Glioma - Cai, Xiaomin; Qiu, Wenjin; Qian, Mengshu; Feng, Shuang; Peng, Chenghao; Zhang, Jiale; Wang, Yi; Wang, Yuhai (Frontiers in Cell and Developmental Biology, 2021)
Objectives: Glioma is the most common and aggressive type of primary central nervous system (CNS) tumor in adults, and associated with substantial mortality rates. The aim of our study was to evaluate the prognostic significance and function of the complement factor I (CFI) in glioma. Materials and methods: The expression levels of CFI in glioma tissues and the survival of the CFI-high and CFI-low patient groups were analyzed using The Cancer Genome Atlas (TCGA) database and Genotype-Tissue Expression (GTEx). The correlation between CFI expression and clinicopathological features of glioma was determined by univariate and multivariate Cox regression analyses in the Chinese Glioma Genome Atlas (CGGA) database. The functional role of CFI in glioma was established through routine in vitro and in vivo assays. Results: CFI is overexpressed in glioma and its high levels correlated with poor outcomes in both TCGA and CGGA datasets. Furthermore, CFI was identified as an independent prognostic factor of glioma in the CGGA database. CFI knockdown in glioma cell lines inhibited growth in vitro and in vivo, whereas its ectopic expression increased glioma cell proliferation, migration and invasion in vitro. CFI protein levels were also significantly higher in the glioma tissues resected from patients, and correlated to worse prognosis. Conclusions: CFI is a potential prognostic biomarker in glioma and drives malignant progression.